The Ethical Framework of Islamic Religious Education Learning Algorithms in Addressing Educational Technology Bias for Strengthening Islamic Character in the Digital Era: Etika Algoritma Pembelajaran PAI dalam Mengatasi Bias Teknologi Pendidikan untuk Penguatan Karakter Islam di Era Digital - Faiz Muzakky; Failasufa Sholihah (Yayasan Nurul Musthafa, 2026)
The development of algorithm driven educational technologies has transformed the ways in which learners comprehend instructional content and engage with religious values within digital spaces. The integration of algorithms into Islamic Religious Education (IRE) introduces latent issues of bias that often remain unrecognized and may impede the internalization of moral character. This study aims to examine the ethical principles of algorithmic systems and to formulate bias mitigation approaches that are aligned with the normative foundations of Islamic education. Employing a qualitative library-based research design, this study synthesizes recent scholarly literature, policy reports, and relevant empirical studies addressing educational technologies in the digital era. The analysis focuses on identifying sources of algorithmic bias and assessing their implications for value-based learning and character formation. The findings indicate that algorithmic bias extends beyond technical dimensions to encompass cultural and pedagogical factors, such as when content recommendation systems overlook learners spiritual contexts or generate unequal access to meaningful learning experiences. By integrating algorithmic ethics with an Islamic moral education framework, this study proposes a bias mitigation model that positions teachers as custodians of values, prioritizes transparency in algorithmic processes, and harmonizes technological use with principles of justice, responsibility, and moral awareness. Technology does not inherently strengthen character; rather, it must be deliberately guided through ethical and value-oriented design to ensure that Islamic Religious Education remains a vital space for the cultivation of spiritual integrity in the digital age. [Perkembangan teknologi pendidikan berbasis algoritma mengubah cara peserta didik memahami materi dan berinteraksi dengan nilai-nilai agama di ruang digital. Integrasi algoritma dalam pembelajaran PAI menyisakan persoalan bias yang kerap tidak disadari dan berpotensi menghambat proses internalisasi akhlak. Penelitian ini bertujuan menelaah prinsip etika algoritma dan merumuskan pendekatan mitigasi bias, selaras dengan karakter pendidikan Islam. Penelitian ini menggunakan metode kualitatif berbasis studi pustaka yang menghimpun literatur mutakhir, laporan kebijakan, serta penelitian relevan terkait teknologi di era digital dalam pendidikan, penelitian ini menganalisis sumber-sumber bias serta implikasinya terhadap pembelajaran nilai dan pembentukan karakter. Temuan menunjukkan bahwa bias algoritmik tidak hanya bersifat teknis, tetapi juga kultural dan pedagogis, misalnya ketika sistem rekomendasi materi mengabaikan konteks spiritualitas peserta didik atau menghasilkan ketimpangan akses terhadap pengalaman belajar bermakna. Penelitian mengintegrasikan etika algoritma dengan kerangka pembentukan akhlak Islami, menghasilkan model mitigasi bias yang menempatkan guru sebagai pengendali nilai, mengutamakan transparansi proses algoritmik, serta menyerasikan teknologi dengan prinsip keadilan, tanggung jawab, dan kesadaran moral. Teknologi tidak otomatis memperkuat karakter, tetapi harus diarahkan melalui desain yang etis dan bernilai, sehingga pembelajaran PAI tetap berfungsi sebagai ruang pengembangan integritas spiritual di era digital.]